Mapping soil carbon sequestration across Argentina and Mexico using roth C. - Reinoso, Verónica; Frolla, Franco Daniel; Ortiz, Sol; Angelini, Marcos Esteban; Cerón, Areli; Beltran, Marcelo Javier; Bunge, Verónica; Peralta, Guillermo Ezequiel; Di Paolo, Luciano Elias; Rodriguez, Dario Martin; Schulz, Guillermo; Velázquez, Juan; et al. (2024)
Presentación en diapositivas